2017
DOI: 10.1038/s41598-017-07355-w
|View full text |Cite
|
Sign up to set email alerts
|

Lipid levels and new-onset diabetes in a hypertensive population: the China Stroke Primary Prevention Trial

Abstract: This study aimed to provide insights into the relationship between lipid levels and new-onset diabetes (NOD) in 14,864 Chinese hypertensive patients without diabetes (6056 men and 8808 women) aged 45–75 years from the China Stroke Primary Prevention Trial (CSPPT, led by Nanfang Hospital, Guangzhou, China). NOD (defined as fasting plasma glucose (FPG) ≥ 7.0 mmol/L at the end of study or self-reported physician diagnosis of diabetes or self-reported use of hypoglycemic agents during follow-up) was analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…These findings are consistent with the fact that very few studies have shown a positive association between preoperative TC levels and NODAT . Whereas elevated LDL‐C and reduced HDL‐C levels were implicated in the development of T2DM, their impact on NODAT requires further clarification.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are consistent with the fact that very few studies have shown a positive association between preoperative TC levels and NODAT . Whereas elevated LDL‐C and reduced HDL‐C levels were implicated in the development of T2DM, their impact on NODAT requires further clarification.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, a 37% increase in the risk of NODAT development was observed with a 1 mmol/L elevation of the preoperative TG level in men, indicating a strong predictive value of the preoperative TG level for NODAT. Dyslipidemia, especially an elevated serum TG level, has long been implicated in the pathogenesis of diabetes in the non‐transplant population; the ADA recommendation that testing for diabetes should be considered in overweight or obese adults with a TG level above 2.82 mmol/L further highlights the positive association between TG and incident diabetes . However, in the transplant setting, the few studies that investigated the association between preoperative TG and NODAT had been conducted mainly in KTRs, and their results are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously assessed the link between plasma lipid parameters and the risk of T2D, highlighting that both high TG and low HDL-C levels are independent risk factors for new-onset T2D in different populations [ 25 , 26 ]. Recently, a large study performed in 451,933 participants of the UK Biobank confirmed that both low HDL-C and apoA-I levels were significantly associated with the risk of new-onset diabetes after multivariable-adjusted regressions and two-sample Mendelian randomization analyses [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of hypertriglyceridemia regarding HbA1c reliability remains uncertain as most evidence stems from in vitro studies or individual cases that report discordant results [8, 9]. In addition, triglyceride levels in these reports (typically >1000 mg/dL) do not represent the concentrations commonly observed in patients with diabetes (150-500 mg/dL) [1113]; in addition, HbA1c was not measured using the accepted standard, HPLC [8, 9]. Still, clinical decisions in the frequent scenario of concurrent hyperglycemia and hypertriglyceridemia have to be made and evaluated in a real-life study; if there is an association between triglyceride levels and HbA1c, it would have important diagnostic and therapeutic implications.…”
Section: Introductionmentioning
confidence: 99%